Job stress and work from home during the COVID-19 pandemic among Japanese workers: a prospective cohort study. Issue 1 (31st December 2023) - Ikegami, Kazunori; Ando, Hajime; Mafune, Kosuke; Tsuji, Mayumi; Tateishi, Seiichiro; Odagami, Kiminori; Muramatsu, Keiji; Fujino, Yoshihisa; Ogami, Akira
ABSTRACT: Objectives: The work style reforms and the coronavirus disease pandemic in Japan have prompted efforts toward teleworking, mainly work from home (WFH). This study aimed to prospectively evaluate the impact of WFH on job stress among Japanese workers. Methods: This online survey-based prospective cohort study was conducted from December 2020 (baseline) to December 2021 (1-year follow-up) using self-administered questionnaires. At baseline, 27, 036 participants completed the questionnaires, whereas 18, 560 (68.7%) participated in the 1-year follow-up. After excluding the 11, 604 participants who left or changed workplaces within 1 year or who were physical laborers and hospitality workers, data from 6, 956 participants were analyzed. We asked participants about WFH frequency at baseline and conducted a follow-up using the Brief Job Stress Questionnaire (BJSQ). Participants were divided into four groups according to WFH frequency. The odds ratios of poor states of the association of the four subscales (job demand, job control, supervisor support, and coworker support) determined by the BJSQ with WFH frequency were estimated using a multilevel logistic model. Results: In both the gender–age adjusted and multivariate models, compared to the non-WFH group, the medium and low WFH groups were less likely to have poor job control, whereas the high WFH group were likely to have similar levels as the non-WFH group. In both models, compared to non-WFH participants, the high WFH group were more likely to have poor supervisor and coworker support. Conclusions: High-frequency WFH requires further attention, because it may increase job stress by exacerbating deficits of social support in the workplace. Medium- and low-frequency WFH workers were more likely to have satisfactory job control; therefore, limiting WFH to three or fewer days per week may lead to better job stress management.